The Slave Woman in the United States of America: A trip from chains and dreams to freedom and nightmares - Morenas López, María Luisa (Journal of Artistic Creation and Literary Research, 2025)
The situation of black women during and after slavery times is a question thathas remained aside due to the seriousness and cruelty of the institution of slavery itself. However, the aim of this paper is to take under close scrutiny the role of women during slavery times, the harsh treatment they were subjected to, and their boundless strength and hope throughout the 250 years in which slavery was legal, contrasted to the so awaited and idealized world without slavery afterwards. In both cases the strong bond of mothers withtheir children will be present, depicting the unconditional love mothers felt towards their beloved, up to the point of doing the unimaginable. To carry out this analysis an interdisciplinary methodology will be used with a socio-cultural approach. In order to illustrate the main theoretical points of this paper, I will provide readings of Toni Morrison’s Beloved, together with that of Harriet Jacobs, Frances Anne Kemble, and Nancy Chodorrow.